Investigating the physiological effects of fungicides on sugar beet growth and yields - Buckley, Annabelle Kate (2025)
Sugar beet (Beta vulgaris subsp. vulgaris) is susceptible to a range of foliar diseases, which can damage the plants and result in significant yield losses. Fungicide programs are routinely used in sugar beet cultivation to gain control of the major foliar diseases and protect plant yields. Some fungicides have been observed to improve the physiology and yields of crops, even in conditions where disease is not present, but this relationship has not yet been determined in sugar beet. This project investigated the relationship between fungicides and sugar beet physiology and yields, to determine the physiological reasons that this process may be occurring.